The answer is:
c = 7s
The Independent Variable is: s
The Dependent Variable is: c
Answer:
y = -3x/2 + 5/2
Step-by-step explanation:
Well, basically what you do is modify it so that y is on one side.
3x+2y = 5
2y = 5-3x
y = (5-3x)/2
y = 5/2 -3x/2
So, the answer is the second option.
Answer:
11
General Formulas and Concepts:
<u>Pre-Algebra</u>
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
<u>Algebra I</u>
Step-by-step explanation:
<u>Step 1: Define</u>
g(x) = x³ - 4
h(x) = x² + 2
h(-2) is x = -2
g(-1) is x = -1
<u>Step 2: Find h(-2) - g(-1)</u>
- Substitute: ((-2)² + 2) - ((-1)³ - 4)
- Exponents: (4 + 2) - (-1 - 4)
- Add/Subtract: 6 - (-5)
- Subtract: 11
Answer:
y = 3x + 1
Step-by-step explanation:
The slope is 3 and the y-intercept is 1, so y= 3x + 1.
Answer:
f^-1(x) = x + 5
Step-by-step explanation:
f(x) = x-5
y = x-5
Exchange x and y
x = y-5
Solve for y
x+5 = y-5+5
x+5 =y
The inverse is x+5